SMOKING AND HEALTH NEWSLETTER (Tufts Archival Research Center, 2007)
The National Interagency Council on Smoking and Health Newsletter for July/August of 1965 launching the publication. Emphasizes goal to serve as a medium of exchange for different groups concerned about the effects of smoking. Includes legislative news regarding the warning labels of cigarette cartons, education programs for children, cessation programs for adults and lists organizations to write to for more information.